Effectiveness of Chlorthalidone Plus Amiloride for the Prevention of Hypertension: The PREVER‐Prevention Randomized Clinical Trial - Sandra Costa Fuchs; Carlos E. Poli‐de‐Figueiredo; José A. Figueiredo Neto; Luiz César N. Scala; Paul K. Whelton; Francisca Mosele; Renato Bandeira de Mello; José F. Vilela‐Martin; Leila B. Moreira; Hilton Chaves; Marco Mota Gomes; Marcos R. de Sousa; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Prehypertension is associated with higher cardiovascular risk, target organ damage, and incidence of hypertension. The Prevention of Hypertension in Patients with PreHypertension (PREVER‐Prevention) trial aimed to evaluate the efficacy and safety of a low‐dose diuretic for the prevention of hypertension and end‐organ damage. Methods and Results This randomized, parallel, double‐blind, placebo‐controlled trial was conducted in 21 Brazilian academic medical centers. Participants with prehypertension who were aged 30 to 70 years and who did not reach optimal blood pressure after 3 months of lifestyle intervention were randomized to a chlorthalidone/amiloride combination pill or placebo and were evaluated every 3 months during 18 months of treatment. The primary outcome was incidence of hypertension. Development or worsening of microalbuminuria, new‐onset diabetes mellitus, and reduction of left ventricular mass were secondary outcomes. Participant characteristics were evenly distributed by trial arms. The incidence of hypertension was significantly lower in 372 study participants allocated to diuretics compared with 358 allocated to placebo (hazard ratio 0.56, 95% CI 0.38–0.82), resulting in a cumulative incidence of 11.7% in the diuretic arm versus 19.5% in the placebo arm (P=0.004). Adverse events; levels of blood glucose, glycosylated hemoglobin, creatinine, and microalbuminuria; and incidence of diabetes mellitus were no different between the 2 arms. Left ventricular mass assessed through Sokolow‐Lyon voltage and voltage‐duration product decreased to a greater extent in participants allocated to diuretic therapy compared with placebo (P=0.02). Conclusions A combination of low‐dose chlorthalidone and amiloride effectively reduces the risk of incident hypertension and beneficially affects left ventricular mass in patients with prehypertension. Clinical Trial Registration URL: http://www.ClinicalTrials.gov, www.ensaiosclinicos.gov. Unique identifiers: NCT00970931, RBR‐74rr6s.